Real-time ENSO forecast skill evaluated over the last two decades, with focus on the onset of ENSO events - Muhammad Azhar Ehsan; Michelle L. L’Heureux; Michael K. Tippett; Andrew W. Robertson; Jeffrey Turmelle (npj Climate and Atmospheric Science)
Abstract This paper provides an updated assessment of the “International Research Institute for Climate and Society’s (IRI) El Niño Southern Oscillation (ENSO) Predictions Plume”. We evaluate 253 real-time forecasts of the Niño 3.4 index issued from February 2002 to February 2023 and examine multimodal means of dynamical (DYN) and statistical (STAT) models separately. Forecast skill diminishes as lead time increases in both DYN and STAT forecasts, with peak accuracy occurring post-northern hemisphere spring predictability barrier and preceding seasons. The DYN forecasts outperform STAT forecasts with a pronounced advantage in forecasts initiated from late boreal winter through spring. The analysis uncovers an asymmetry in predicting the onset of cold and warm ENSO episodes, with warm episode onsets being better forecasted than cold onsets in both DYN and STAT models. The DYN forecasts are found to be valuable for predicting warm and cold ENSO episode onsets at least several months in advance, while STAT forecasts are less informative about ENSO phase transitions. The results indicate that predicting ENSO onset is challenging and that the ability to do so is both model- and event-dependent.